Prognostic value of CBV index in patients with acute ischemic stroke treated with endovascular thrombectomy in late therapeutic window - Sun, Aicheng; Cao, Yuezhou; Jia, Zhenyu; Zhao, Linbo; Shi, Haibin; Liu, Sheng (Frontiers in Neurology, 2024)
Purpose To evaluate the prognostic value of the cerebral blood volume (CBV) index for 90-day functional outcomes in patients with acute ischemic stroke (AIS) treated within a late therapeutic window. Methods We retrospectively reviewed patients who underwent pre-treatment computed tomography perfusion (CTP) and endovascular thrombectomy (EVT) for large-vessel occlusion (LVO) of the anterior circulation within the late therapeutic window between January 2021 and February 2023. Clinical data, the Alberta Stroke Program Early Computed Tomography Score (ASPECTS) based on unenhanced computed tomography (CT), and perfusion parameters, including ischemic core, hypoperfusion volume, mismatch volume between the core and penumbra, and CBV index, were assessed and compared between patients who achieved favorable outcomes (defined as a modified Rankin Scale score of 0–2). Results Of the 118 patients, 56 (47.5%) had favorable outcomes. In the univariate analysis, age, National Institutes of Health Stroke Scale (NIHSS) score at admission, ASPECTS score, CBV index, and ischemic core volume were significantly associated with functional outcomes (P < 0.05). In multivariate analyses, age (odds ratio [OR], 1.060; 95% confidence interval [CI] 1.013–1.110, P = 0.012), NIHSS score at admission (OR, 1.126; 95% CI 1.031–1.229, P = 0.009), and CBV index (OR, 0.001; 95% CI 0.000–0.240, P = 0.014) were independent predictors of a 90-day favorable outcome. Conclusion A high CBV index was independently associated with favorable outcomes in patients who underwent mechanical thrombectomy within the late therapeutic window. In addition, a higher CBV index reflects improved blood flow and favorable digital subtraction angiography collateral status.